The benefits of regular cardiac coherence: results of a preliminary study conducted in the French primary schools of the island of Réunion - Vauthier, Michaël; Guarino, Alessio; Stefanelli, Federica (Formazione & insegnamento, 2019)
This preliminary study presents the results regarding the implementation of a cardiac coherence practice in some classes belonging to elementary schools on the island of Reunion. Cardiac coherence is a physiological condition characterized by the balance of the two branches that make up the autonomic nervous system: the sympathetic nervous system, which is responsible for the behavioral response “attack or flight”, and the parasympathetic nervous system, which intervenes in the resting phases, relaxation, digestion and recovery. The research involved an overall sample of 35 teachers. The results highlight how the regular practice of cardiac coherence with synchronous breathing carried out in the classroom is useful in promoting the quality of life perceived by both teachers and students.